PERANAN KERAPATAN ADAT NAGARI (KAN) DALAM PENYELESAIAN SENGKETA TANAH ULAYAT (Studi kasus pada KAN Sungai Buluah, Kecamatan Batang Anai, Kabupaten Padang Pariaman) - , Yeni Marlina ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research concerning the Role of Kerapatan Adat Nagari (KAN) on Lawsuit Settlement of the Ulayat Ground (Case Study on KAN of Sungai Buluah, Sub District of Batang Anai, District of Padang Pariaman) has aim to find out the lawsuit settlement process of ulayat ground in Kenagarian Sungai Buluah, role of KAN on lawsuit settlement of the ulayat ground in Kenagarian Sungai Buluah and the constraints encountered by KAN of Sungai Buluah on the lawsuit settlement of ulayat ground.. This research uses empirical-yuridical (socio-legal research) or nondoctrinal approach. It is an empirical data searching activity, using scientific method, merging systematically between deductive and inductive way of thinking. The primary data collecting technique is done through field research using direct communication technique with interview. The interview used is unstructured interview by meanof focused interview. To complete the data is also done the library research, the technique used in secondary data collection is documentary study technique, with instrument of written materials, while the research subject consisted of the informant and respondent as much as 18 (eighteen) peoples. Based on the result can be concluded that the lawsuit settlement process of ulayat ground in Kenagarian Sungai Buluah, Sub District of Batang Anai, District of Padang Pariaman based on habitual âberkamar kecil, berkamar besarâ (having small and big room) can not take an agreement, then settled by KAN, the role of KAN on lawsuit settlement of ulayat ground in Kenagarian Sungai Buluah is well done by applying principle of Customary Law that is: âbertangga naik bertangga turunâ (having up and down stepsâ) with parable âmenarik rambut dalam tepung, rambut tidak putus, tepung tidak tumpah,â (pull the hair in flour, the hair not severed, the flour not spilled) with âpola kita sama kitaâ, (pattern among us) in fom of reconciliation, as well as the pusako (heirloom) problem dan sako (custom title).